Analisis Pengaruh Kebijakan Deviden Terhadap Harga Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Febi Berliana; Aris Munandar; Hanifah Muthiah (Sharing: Journal of Islamic Economics Management and Business, 2025)
This study aims to analyze the effect of dividend policy on stock prices of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Dividend policy is considered an important factor in financial management because it can provide positive or negative signals to investors regarding a company’s prospects. This study employs a quantitative approach with a sample of five manufacturing companies in the basic materials sector selected through purposive sampling. The data were obtained from annual financial statements published on the official IDX website. The analytical technique used is panel data regression, preceded by classical assumption tests as prerequisites. The results show that dividend policy, measured by the Dividend Payout Ratio (DPR), has a positive and significant effect on stock prices, which are measured by the Price Earnings Ratio (PER). This is evidenced by a t-test significance value of 0.006 < 0.05 and an R² value of 27.4%, indicating that the dividend policy variable explains 27.4% of the variation in stock prices, while the remaining variation is influenced by other factors. These findings confirm that dividend policy plays an important role in shaping investor perceptions and influencing the market value of a company. This study is expected to provide insights for company management in making profit distribution decisions and for investors in determining more rational investment strategies.